PENINGKATAN HASIL PRESTASI MENGAJAR GURU DENGAN MENERAPKAN MODEL PEMBELAJARAN POWER OF TWO - Dompak Sitorus (JURNAL PENA EDUKASI, 2019)
Abstract: The results of the teacher's teaching ability by applying the Power Two learning model have increased. Before the school action was implemented the average value of the teacher's science subjects in the school was 48,500 with a standard deviation of 9,021. After the action in the first cycle, the teacher's teaching outcome scores averaged 71,800 and the standard deviation was 10,792. Likewise, in the second cycle the average teacher teaching outcome increased, namely 80,600 in the good category with a standard deviation of 8,180. Before the action was carried out the category of the average teacher teaching outcomes was in the low category with a completeness rate of 48.50% (Of the 40 teachers only one was completed). In the first cycle after the action was carried out the teacher's teaching results were in the moderate category with a completeness rate of 71.80% (25 people completed from 40 teachers). In the second cycle after further actions were taken as a result of reflection the first cycle of teacher teaching results was in the high category (average value 80.60) with a percentage of 95% completeness. Keyword: Teacher Teaching Achievements, Power of Two Learning Models Abstrak: Hasil kemampuan mengajar guru dengan menerapkan model pembelajaran Power Two menjadi meningkat. Sebelum dilaksanakan tindakan sekolah nilai rata-rata mata pelajaran IPA guru di sekolah adalah 48,500 dengan simpangan baku 9,021. Setelah dilakukan tindakan pada siklus I nilai hasil mengajar guru rata-ratanya menjadi 71,800 dan standar deviasi 10,792. Demikian pula pada siklus II rata-rata hasil mengajar guru terjadi peningkatan, yaitu 80,600 berada pada kategori baik dengan simpangan bakunya 8,180. Sebelum dilakukan tindakan kategori rata-rata hasil mengajar guru berada pada kategori rendah dengan tingkat ketuntasan 48,50 % (Dari 40 orang guru hanya satu orang yang tuntas). Pada siklus I setelah dilakukan tindakan hasil mengajar guru berada pada kategori sedang dengan tingkat ketuntasan 71,80 % (25 orang yang tuntas dari 40 guru). Pada siklus II setelah dilaksanakan tindakan lebih lanjut sebagai hasil dari refleksi siklus I hasil mengajar guru berada pada kategori tinggi (nilai rata-rata 80,60) dengan presentase tingkat ketuntasan 95%. Kata kunci: Prestasi Mengajar Guru, Model Pembelajaran Power Of Two